Pengembangan Permainan Papabov untuk Pembelajaran Bola Voli Siswa Sekolah Dasar (Universitas Negeri Semarang, 2022)
The purpose of this research is to produce the development of a papabov game model for volleyball learning for elementary school students and testing the effectiveness of the papabov game model for volleyball learning in elementary school students.This study uses research and development research methods. The research subjects involved 36 students for small-scale trials and 73 students for large-scale trials. The instruments used in data collection are in the form of expert evaluation sheets, student questionnaire sheets for cognitive, affective and psychomotor assessments. The data analysis technique used in this development research is to use descriptive analysis techniques in the form of percentages.The results of the analysis of the data obtained from the evaluation of volleyball experts, obtained an average rating of 87.34% (Good). Evaluation of physical education learning experts, obtained an average rating of 91.11% (very good). The results of the analysis of small-scale trial data obtained a percentage of 88.89% (good). The results of the analysis of large-scale trial data obtained the percentage of appropriate answer choices 93.23% (very good).Based on the results of research and discussion in this skipsi, it can be concluded that the Papabov game learning model product is effectively used in volleyball lessons for fifth graders at SD Negeri 1 Donosari, SD Negeri 2 Jambearum and SD Negeri 3 Jambearum.